New unitary space-time codes with high diversity products - Niyomsataya, Terasan (University of Ottawa (Canada), 2004)
We propose new unitary space-time codes with high diversity products for multiple antenna wireless communications. These Hamiltonian and product constellations have full diversity, and can be used for any number of transmitter antennas and for any data rate. Hamiltonian constellations for-two transmitter antennas are based on Slepian's group codes. We construct Hamiltonian constellations for any M transmitter antennas by using a direct sum of 2 x 2 Hamiltonian matrices for M even, and a direct sum of 2 x 2 Hamiltonian matrices with the roots of unity for M odd. Product constellations are proposed using a product of a Hamiltonian constellation and a representation of cyclic group. We also present product constellations of two Hamiltonian constellations with diagonal blocks in different order for M odd. Many of our constellations outperform, and have higher diversity products, than the best known space-time constellation designs in the literature.
Keywords: Engineering, Electronics and Electrical.